2018
DOI: 10.1080/10407782.2018.1459139
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of double-diffusive mixed convection and entropy generation in a lid-driven trapezoidal enclosure with a heat source

Abstract: The version presented here may differ from the published version or, version of record, if you wish to cite this item you are advised to consult the publisher's version. Please see the 'permanent WRAP URL' above for details on accessing the published version and note that access may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…The findings revealed that the effects of the moving lid became negligible for , although the increasing Rayleigh number led to more excellent streamline circulation and dominant convection effects within the enclosure. While in another investigation, the results indicated that the average Nusselt number decreased as the Lewis number increased, while the total entropy production increased 15 . Al-Rashed et al 16 examined mixed convection and entropy generation in a cubical heated up by a central isothermal block.…”
Section: Introductionmentioning
confidence: 85%
“…The findings revealed that the effects of the moving lid became negligible for , although the increasing Rayleigh number led to more excellent streamline circulation and dominant convection effects within the enclosure. While in another investigation, the results indicated that the average Nusselt number decreased as the Lewis number increased, while the total entropy production increased 15 . Al-Rashed et al 16 examined mixed convection and entropy generation in a cubical heated up by a central isothermal block.…”
Section: Introductionmentioning
confidence: 85%
“…In this work, the irreversibility coefficient ratios ( φ i , 1 ≤ i ≤ 3) are taken as φ 1 = 10 −4 , φ 2 = 0.5 and φ 3 = 10 −2 (Mchirgui et al , 2012; Oueslati et al , 2013; Ababaei et al , 2018; Hussain et al , 2018). The total entropy generation ( S T ) is defined as follows: …”
Section: Entropy Generation Analysismentioning
confidence: 99%
“…Three different entropy parameters can be written in dimensionless form as follows (Ababaei et al, 2018;Hussain et al, 2018):…”
Section: Entropy Generation Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, Chamkha and Ismael (2016) studied the dampening effect of magnetic fields on thermal behavior. Mixed convection under the double-diffusion of air (Pr = 0.7) filled right-angled trapezoidal enclosure (with inward side angles of 45º and 60º) heated partially has been investigated by Ababaei et al (2018) and observed that heat and mass transfer were significantly affected by the side angle as well as flow control parameters. using different types of nanofluids, Kareem et al (2016) examined the bottom heated inclined trapezoidal cavity (with side angle 30º–60º) with a moving cold top wall and found that heat transfer is more with higher nanoparticle concentration and at a lower rotational angle.…”
Section: Introductionmentioning
confidence: 99%